Chloroplast genome of Corydalis impatiens (Pall.) Fisch. ex DC. (Papaveraceae), a Tibetan medical herb - Digao Wan; Haijuan Bao; Qupei Danzeng; Xiao Guo; Qien Li (Mitochondrial DNA. Part B. Resources, 2022)
Corydalis impatiens (Pall.) Fisch. 1821. (Papaveraceae) is a Tibetan medical herb used to reduce pain, treat skin injuries, cure hepatitis, and benefit the circulatory system. In the current study, the chloroplast genome of C. impatiens was sequenced. This complete genome is a circular 197,317 bp sequence consisting of a small single-copy (SSC, 3105 bp) region, a large single-copy (LSC, 89,790 bp) region, and a pair of inverted repeats (IRs, 52,211 bp). This chloroplast genome encodes a total of 127 functional genes, including 81 protein-coding, 38 transfer RNA, and eight ribosomal RNA genes. Furthermore, this chloroplast genome contains six pseudogenes, including a pair of ndhB a pair of ndhD, one ndhC, and one ndhK. The phylogenetic relationship within the genus Corydalis was inferred with the maximum-likelihood method, and the result showed that C. impatiens was most closely related to C. conspersa.